2014
DOI: 10.1039/c3py01244a
|View full text |Cite
|
Sign up to set email alerts
|

A new proton sponge polymer synthesized by RAFT polymerization for intracellular delivery of biotherapeutics

Abstract: A spermine-like polymer was synthesized via reversible addition-fragmentation chain transfer polymerization as a potential endosomal escaping agent. A new methacrylate monomer, 2-((tertbutoxycarbonyl)(2-((tert-butoxycarbonyl)amino)ethyl)amino)ethylmethacrylate (BocAEAEMA), was prepared and then polymerized via RAFT polymerization at constant monomer or initiator concentration increase in M n with monomer conversion was also observed. P(BocAEAEMA)s with controlled molecular weights and narrow molecular weight d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Three different commercially available amino methacrylates that have tertiary (DMAEMA), secondary ( t BAEMA) and protonated primary amine functionalities (AEMA · HCI) were used as comonomers. The utilized CTA CPADB has previously been successfully applied to mediate the RAFT polymerization of amino methacrylates . [M]/[CTA] was kept constant at a ratio of 100/1 with a monomer concentration of 2 mol L −1 in order to obtain relatively low molar mass polymers, considering the increased toxicity of high molar mass polycations .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three different commercially available amino methacrylates that have tertiary (DMAEMA), secondary ( t BAEMA) and protonated primary amine functionalities (AEMA · HCI) were used as comonomers. The utilized CTA CPADB has previously been successfully applied to mediate the RAFT polymerization of amino methacrylates . [M]/[CTA] was kept constant at a ratio of 100/1 with a monomer concentration of 2 mol L −1 in order to obtain relatively low molar mass polymers, considering the increased toxicity of high molar mass polycations .…”
Section: Resultsmentioning
confidence: 99%
“…A series of amino-functionalized PMMA based copolymers was synthesized via RAFT polymerization due to its versatility and suitability for the synthesis of well-defined amino methacrylate copolymers. 28,29 Three different commercially available amino methacrylates that have tertiary (DMAEMA), secondary (tBAEMA) and protonated primary amine functionalities (AEMAÁHCI) were used as comonomers. The utilized CTA CPADB has previously been successfully applied to mediate the RAFT polymerization of amino methacrylates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…52,53,54 Compared to other controlled radical polymerizations (CRP), such as nitroxide-mediated polymerization (NMP) and atom transfer radical polymerization (ATRP), RAFT polymerization excels in its versatility. 55,56,57 A wide variety of (functional) monomers can be prepared by RAFT polymerization in different solvents under mild reaction conditions. Finally, the technique' s high end-group fidelity at reasonably high conversion (80 %) offers the opportunity for pre-and post-functionalization, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Their controllable size distributions also make it possible to obtain macromolecules small enough to penetrate vascular defects of solid tumor as well as large enough to prevent renal clarification permitting longer bioavailability 10,13 . Besides, they are suitable to be further modified for targeting and/or imaging purposes 14,15,16,17 . In our previous study, we have shown that PMMA-b-PHEMA micelles can further be modified with arginylglycylaspactic acid (RGD) and Trans-Activator of Transcription (TAT) peptide to enhance cell selectivity and membrane penetration properties 7 which is similar to peptide modified conducting polymer structures in the field of biobased covering materials 18,19 .…”
Section: Introductionmentioning
confidence: 99%